2005
DOI: 10.2131/jts.30.239
|View full text |Cite
|
Sign up to set email alerts
|

Practical Application of Guinea Pig Telemetry System for Qt Evaluation

Abstract: The purpose of this study was to evaluate a telemetry system for examining QT evaluation in the conscious free-moving guinea pig using 10 reference compounds whose effects on human QT interval are well established: 8 positive references (bepridil, terfenadine, cisapride, haloperidol, pimozide, quinidine, E-4031 and thioridazine), and 2 negative references (propranolol and nifedipine). Pharmacokinetic experiments were also performed for the 8 positive references. Telemetry transmitters were implanted subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…Guinea-pigs are a model for electrophysiological and pharmacological investigations (Farraj et al 2011). In vivo guinea-pig models were studied over the years, both with conscious (Shiotani et al 2005) and anesthetized animals (Morissette et al 2013). This model is especially used to evaluate new drugs before they are allowed for commercialization, particularly those with high risk of arrhythmias and/or alterations of QT interval (Tárraga et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Guinea-pigs are a model for electrophysiological and pharmacological investigations (Farraj et al 2011). In vivo guinea-pig models were studied over the years, both with conscious (Shiotani et al 2005) and anesthetized animals (Morissette et al 2013). This model is especially used to evaluate new drugs before they are allowed for commercialization, particularly those with high risk of arrhythmias and/or alterations of QT interval (Tárraga et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, as compared to the anesthetized guinea-pig model, there are relatively few reports on cardiovascular effects of drugs obtained from conscious guinea-pigs, particularly from studies using telemetry. This lack of in vivo data can be explained at least partly by the difficulties to achieve proper anesthesia/surgery and appropriate placement of ABP catheters in guinea-pigs as compared to other species [98][99][100][101]. Some teams use restrained conscious guinea-pigs, maintained quiet in slings, to assess the proarrhythmic liabilities of drugs.…”
Section: In Vivo Studies For Tdp Assessmentmentioning
confidence: 99%
“…Some pharmaceutical laboratories have already adopted the telemetered conscious guinea-pig in their screening strategies as a valuable tool for assessing the arrhythmogenic potential of new drug candidates in the early stage of drug development. This model has been shown as suitable to detect QTc prolongation induced by various therapeutic classes-related compounds including antiarrhythmic agents (quinidine, sotalol, dofetilide, bepridil), antihistaminics (terfenadine), prokinetics (cisapride), or psychiatric drugs (haloperidol, pimozide, thiodazine), along with possible T wave shape modifications, or the absence of any QTc changes with negative controls [100,101]. Importantly, whatever the guinea-pig model used, i.e., anesthetized versus conscious, the choice of appropriate methods for correcting QT interval versus heart rate is crucial to correctly evaluate QTc changes.…”
Section: In Vivo Studies For Tdp Assessmentmentioning
confidence: 99%
“…Although QT prolongation and/or torsades de pointes caused by coadministration of terfenadine and ketoconazole has been studied in animals and humans [16,17], most of the studies were done in anesthetized animals [1,4,5]. With the use of a telemetry system, experimentation can be performed on conscious unstressed animals [7,13,[19][20][21]. Few studies have reported the ef-fects of drug-induced QT interval prolongation in conscious guinea pigs using a telemetry system [7,21].…”
Section: Introductionmentioning
confidence: 99%
“…With the use of a telemetry system, experimentation can be performed on conscious unstressed animals [7,13,[19][20][21]. Few studies have reported the ef-fects of drug-induced QT interval prolongation in conscious guinea pigs using a telemetry system [7,21]. Among them, a high dose of ketoconazole (400 mg/kg, po) administered to guinea pigs induced a significant prolongation of the QTc interval [7].…”
Section: Introductionmentioning
confidence: 99%